Perbandingan Hubungan Keperdataan Antara Ayah dan Anak Biologis: Studi Komparatif Indonesia, Malaysia, dan Kuwait - Abd Rahman Hidayat; Muhammad Handika Suryanto; Fatma Tria Arresti (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to compare civil relations between biological fathers and children in Indonesia, Malaysia and Kuwait. Through a comparative study approach, this research seeks to analyze the differences and similarities in the civil system that regulates the rights and obligations of fathers towards their biological children. In analyzing the data, a contextual comparative approach was used to understand the legal system that shapes the civil relationship between biological fathers and children in Indonesia, Malaysia and Kuwait. The results of this study show that there are significant differences between the two regions in terms of civil arrangements for biological fathers and children. Indonesia and Malaysia have more opportunities to recognize the rights and obligations of fathers towards biological children, while in Kuwait, the influence of religious and traditional factors play an important role in regulating these relationships. Apart from that, it was also found that there were differences in the legal recognition of the status of biological fathers and the legal protection given to biological children in the three countries.